Investment Feasibility Analysis For Distribution Network Development of PDAM Tirta Bening Lontar Kupang City - Rival Sibuea, Josep; Oetomo, Wateno; Marleno, Risma (Devotion : Journal of Research and Community Service, 2022)
Clean water is the most basic need for humans and other living things. In Indonesia, the government's responsibility for fulfilling clean water is regulated in article 5 of Law Number 7 of 2004 concerning Water Resources, where the state guarantees everyone's right to obtain water for minimum daily basic needs in order to fulfill a healthy, clean life. and productive. The purpose of the research based on the formulation of the problems that occur is to determine the feasibility analysis of investment in the distribution network development of PDAM Tirta Bening Lontar in Penkase Oeleta Village, Alak District, Kupang City, in terms of financial, social and economic aspects. Data collection methods used in this research are observation and literature study. Feasibility Investment Analysis using the Pay Back Period (PBP) Method, Net Present Value (NPV) Method, Internal Rate Of Return (IRR) Method, Probability Ratio (PR) and Break Event Point (BEP). Based on the results of the analysis and discussion regarding the feasibility analysis of the investment from the financial aspect with an investment assessment: Net Present Value (NVP), Benefit Cost Ratio (BCR), Payback Period (PP) and Internal Rate Of Return (IRR) the project is feasible to implement. (NPV > 0) so the project is feasible to continue. If BCR ≥ 1, then it is said that the project is acceptable or feasible. The payback period is 4.24 years. The criteria for analyzing social and economic aspects are for regional development funds 30% and general reserve funds 15% including regional development funds of Rp. 39,515,617.00 and a general reserve fund of Rp. 19,757,809.00.